Pecan-medicinal crops intercropping improved soil fertility and promoted interactions between soil microorganisms and metabolites - Ruyuan Wang; Chenyang Liu; Xuesong Bie; Yan Dai; Xu Feng; Ren Wang; Ming Wang; Shu Xu; Yu Chen (Chemical and Biological Technologies in Agriculture)
Abstract Background Pecan [Carya illinoinensis (Wangenh.) Koch] is a widely cultivated dried fruit and woody oil tree with high economic value. Continuous sole planting of pecan caused some land to lie idle and deterioration of soil conditions. Tree and medicinal crops intercropping represents an environmental-friendly and economically feasible solution to these issues. Thus, we aimed to explore the underlying mechanism by which intercropping improved soil condition by regulating the interactions of the soil microbiome and metabolome. In this study, pecans were intercropped with medicinal crops caper spurge and honeysuckle on a tree farm in China. A combined analysis of soil microbiomes and metabolomes was performed to discover the effects of intercropping on bulk and rhizosphere soils. Results The results showed that intercropping improved the edaphic properties of bulk soil and promoted the growth of pecan and caper spurge. Intercropping also significantly altered the structures of both bacterial and fungal communities in bulk soil, stabilised the enrichment of nitrogen-cyclic bacteria, for instance, Bacillus, and decreased the relative abundances of plant–pathogenic fungi, for instance, Fusarium. In addition, the result of metabolomic analysis showed that intercropping promoted the synthesis of functional compounds, such as trehalose and ethanolamine, which enhanced plant disease resistance in bulk soils. Moreover, the co-occurrence networks of microbiomes and metabolomes of bulk soils revealed that Bacillus was significantly correlated with Fusarium, Alternaria, and trehalose under intercropping patterns. Furthermore, analysis of microbiomes and metabolomes in the rhizosphere soil of caper spurge and honeysuckle revealed that Penicillium and Rhizomicrobium were significantly increased by intercropping and showed more dynamic connections with other genera and metabolites compared with single planting. Conclusions Overall, intercropping pecans with caper spurge and honeysuckle can improve soil conditions and promote plant growth through microbiological and metabolomics integrated analyses. This study provides valuable information and theoretical basis for optimizing land resource utilisation and improving soil conditions in tree fields like pecan fields via intercropping, thereby reducing production losses and ensuring economic benefits. Graphical Abstract